2004
DOI: 10.1159/000081679
|View full text |Cite
|
Sign up to set email alerts
|

Ileo-Neorectal Anastomosis: Medium- and Long-Term Follow-Up of 37 Patients

Abstract: Background: Ileo-neorectal anastomosis (INRA), an alternative restorative procedure, was developed to reduce the pouch-related complication rate with an (at least) equal functional result. Methods: For this surgical outcome, data of all INRA patients, including bowel function and complications, were prospectively recorded. The reservoir capacity was determined repeatedly by physiologic tests. The anal sphincter complex was assessed by manometry and ultrasound examination. Evaluation of the neorectal mucosa was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
2
5
0
Order By: Relevance
“…In the patients who had a functioning INRA longterm function was constant over time, being similar to that reported by us in 2004 over a shorter interval from surgery [35]. In addition the present study showed that QoL and HS were comparable to the healthy population.…”
Section: Discussionsupporting
confidence: 90%
“…In the patients who had a functioning INRA longterm function was constant over time, being similar to that reported by us in 2004 over a shorter interval from surgery [35]. In addition the present study showed that QoL and HS were comparable to the healthy population.…”
Section: Discussionsupporting
confidence: 90%
“…Functional results at this stage were comparable to those reported in the literature for IPAA [5]. [3,6] (Fig. 1).…”
Section: Introductionsupporting
confidence: 88%
“…Patient follow up with data registration was as described previously. All results were compared with the results of the 2-year follow up [6].…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, it has been reported that the MBP and the MSP improve after ileostomy closure[36,44]. For example an increase in the RC over time after ileo‐neorectal anastomosis has been described [45]. These findings suggest that our model may predict to poor an outcome following stoma reversal.…”
Section: Discussionmentioning
confidence: 66%